PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MUTU PEMBELAJARAN DI SMA MUHAMMADIYAH TANAH GROGOT - Annisa Mardhatillah; Elisa Novianur Fitriani; Siti Ma’rifah; Adiyono (CV. ADIBA ASIHA AMIRA, 2022)
This study aims to describe the development of Islamic Religious Education curriculum at SMA Muhammadiyah, Tanah Grogot. This research method uses qualitative research. The research data was obtained from the results of interviews with Islamic Religious Education teachers at Muhammadiyah High School. The results of the study found that the development of the Islamic Religious Education curriculum at SMA Muhammadiyah, Tanah Grogot, namely 1) Using the Ismuba curriculum designed by the PP Muhammadiyah Dikdasmen 2) Learning materials, namely PAI and Arabic added with kemuhammadiyahan education 3) Applying principles which are basically the same as others include applying the principles of relevance, flexibility, sustainability, practicality and effectiveness 4) Using learning methods such as lectures, discussions, practice and assignments 5) Using the assignment video script method during the covid-19 pandemic 6) Using a critical approach to students, that is, they really like to provoke students to think 7) The evaluation used is the evaluation of learning outcomes, from the exam process (both mid-semester exams and semester exams. The data above is an effort to develop the PAI curriculum in order to improve the quality of PAI learning in SMA Muhammadiyah